3D-VIEWER: An Atlas-Based System for Individual and Statistical Investigations of the Human Brain - Berks, G.; Pohl, G.; Keyserlingk, D. Graf v. (Methods of Information in Medicine, 2001)
3D-VIEWER is a new software tool for neurosurgical planning and population studies. It is based on digitized three-dimensional brain atlases derived from standard stereotactic atlases that can be adapted to an individual’s brain and shown as a series of displayed images. If the patient’s brain has been imaged in different modalities, the standardized anatomical information can be adapted to the individual images, which will bring the images into registration. The 3D-VIEWER can be used as a tool for combining multimodal information from the same patient. In addition, several tools are available that allow oblique views of anatomical structures or the view along the intended trajectory during a neurosurgical intervention. Furthermore, using the atlas transformation matrices, anatomical information can be determined when comparing an individual’s brain to the anatomy of the atlas brain. Thus, standardized anatomical information from the atlas can be introduced into individual images. This standardization is used to perform individual-group and group-by-group comparisons between patients and normal controls in anatomical studies.
Keywords: Brain Atlas; Multimodal Registration; Neurosurgical Planning; Intersubject Standardization